2017
DOI: 10.1016/j.ram.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of growth of Aspergillus spp. from agricultural soils in the presence of glyphosate

Abstract: Agriculture is one of the bases of the Argentine economy. Glyphosate is undoubtedly one of the most important herbicides used. The increasing consumption and the efficiency of glyphosate-based herbicides have encouraged several studies on their persistence in soils, their effects on soil microbiota and their degradation processes. Fungi have been reported as being the main herbicide-degrading microorganisms as well as the most tolerant to environmental stress conditions. This study evaluated the growth perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
3
13
0
1
Order By: Relevance
“…The biomass assay described by Arfarita et al (Arfarita et al, 2011) have previously been used as a robust methodology for the screening of microorganisms able to use glyphosate as nutrient source. A similar conclusion about this methodology was reached out by other workers with similar design (Arfarita et al, 2016;Carranza et al, 2016Carranza et al, , 2017. The selected isolate Penicillium 4A21 degraded the herbicide glyphosate by over 42% in just 14 days in submerged fermentation.…”
Section: Discussionsupporting
confidence: 73%
“…The biomass assay described by Arfarita et al (Arfarita et al, 2011) have previously been used as a robust methodology for the screening of microorganisms able to use glyphosate as nutrient source. A similar conclusion about this methodology was reached out by other workers with similar design (Arfarita et al, 2016;Carranza et al, 2016Carranza et al, , 2017. The selected isolate Penicillium 4A21 degraded the herbicide glyphosate by over 42% in just 14 days in submerged fermentation.…”
Section: Discussionsupporting
confidence: 73%
“…A proteomic analysis indicated protein expression modulation and possible metabolic disturbances . Similar effects were not observed for Aspergillus section Flavi strains and A. niger (Carranza et al, 2017). Negative effects of glyphosate and/or N fertilization on soil enzymes and arbuscular mycorrhizal fungi were reported (Nivelle et al, 2018).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humasupporting
confidence: 65%
“…Xenobiotic compounds, such as pesticides, also have a considerable effect on fungal development. Previous studies have shown significant changes on both growth rate and mycotoxin production of Aspergillus species caused by GP …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown significant changes on both growth rate and mycotoxin production of Aspergillus species caused by GP. [10][11][12][13][14][15] Several maize (Zea mays L.) diseases can affect yield, nutritive value, and quality of the grains. Fusarium sp.…”
Section: Introductionmentioning
confidence: 99%